2015
DOI: 10.1590/0103-8478cr20130350
|View full text |Cite
|
Sign up to set email alerts
|

Detecção de Meloidogyne enterolobii em mudas de amoreira (Morus nigra L.)

Abstract: Detecção de Meloidogyne enterolobii em mudas de amoreira (Morus nigra L.).Ciência Rural, v.45, n.5, mai, 2015.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…Guangdong, Guangxi, and Hunan was M. enterolobii, which is consistent with the results reported by Paestakahashi et al (2015) in Brazil and by Long et al (2019) in Hainan province of China based on morphological and molecular characteristics. However, Chen (1989a, 1989b) identified pathogens of mulberry root-knot nematode disease in Shanxi as Meloidogyne arenaria, Meloidogyne incognita, Meloidogyne javanica, and Meloidogyne thamesi, while Tang et al (2002) identified pathogen of mulberry root-knot nematode disease as M. incognita and Meloidogyne arenaria in Yunnan based on the female perineal pattern, anal characteristics, male posture, tail length, and stylet of J2.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Guangdong, Guangxi, and Hunan was M. enterolobii, which is consistent with the results reported by Paestakahashi et al (2015) in Brazil and by Long et al (2019) in Hainan province of China based on morphological and molecular characteristics. However, Chen (1989a, 1989b) identified pathogens of mulberry root-knot nematode disease in Shanxi as Meloidogyne arenaria, Meloidogyne incognita, Meloidogyne javanica, and Meloidogyne thamesi, while Tang et al (2002) identified pathogen of mulberry root-knot nematode disease as M. incognita and Meloidogyne arenaria in Yunnan based on the female perineal pattern, anal characteristics, male posture, tail length, and stylet of J2.…”
Section: Discussionsupporting
confidence: 92%
“…Root-knot nematode disease has dramatically impacted Morus alba L. production in Japan, India, and Brazil (Hida and Zhu, 1985;Sujathamma et al, 2014;Paestakahashi et al, 2015). According to Chen (1989a, 1989b), root-knot nematodes cause mulberry leaf loss of 20 to 45%, with severe cases reaching over 75% in some fields Chen, 1989a, 1989b).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several Meloidogyne species have been reported parasitizing mulberry worldwide. In China, M. enterolobii [7], in Japan, M. mali [8], in India, M. incognita [9], in Brazil, M. incognita and M. javanica [10], and, also in Brazil, M. enterolobii was described parasitizing Morus nigra (blueberry) [11]. These reports highlight the importance and distribution of root-knot nematodes in mulberry growing regions worldwide.…”
Section: Open Accessmentioning
confidence: 99%
“…saccharinus, Ipomoea aquatica Forssk, and Morinda citrifolia (Liao, 2001;Brito, 2007;Rammah, 1988). Paestakahashi et al (2015) were the rst to report parasitic damage caused by M enterolobii on mulberry in Brazil. Subsequent morphological and molecular analyses conducted by Zhang et al (2020) identi ed M enterolobii as the pathogen responsible for mulberry infections in the Guangdong Province.…”
Section: Introductionmentioning
confidence: 99%